2022
DOI: 10.1038/s41598-022-26047-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IMERG and ERA5 precipitation products over the Mongolian Plateau

Abstract: Precipitation is an important component of the hydrological cycle and has significant impact on ecological environment and social development, especially in arid areas where water resources are scarce. As a typical arid and semi-arid region, the Mongolian Plateau is ecologically fragile and highly sensitive to climate change. Reliable global precipitation data is urgently needed for the sustainable development over this gauge-deficient region. With high-quality estimates, fine spatiotemporal resolutions, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 113 publications
2
17
0
Order By: Relevance
“…However, IMERG is produced by merging the precipitation estimates with highest quality passive microwave sensors and infrared sensors. It thus can be regarded as the state‐of‐the‐art observational precipitation product (Li et al., 2023; W. Ma, Chen, & Guan, 2020; Watters et al., 2021; Xin et al., 2022). Compared to IMERG, it has been well known that models have trouble simulating the precipitation realistically (D. Chen et al., 2021; Christopoulos & Schneider, 2021; Frei et al., 2003; H. Kim et al., 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IMERG is produced by merging the precipitation estimates with highest quality passive microwave sensors and infrared sensors. It thus can be regarded as the state‐of‐the‐art observational precipitation product (Li et al., 2023; W. Ma, Chen, & Guan, 2020; Watters et al., 2021; Xin et al., 2022). Compared to IMERG, it has been well known that models have trouble simulating the precipitation realistically (D. Chen et al., 2021; Christopoulos & Schneider, 2021; Frei et al., 2003; H. Kim et al., 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It thus can be regarded as the state-of-the-art observational precipitation product (Li et al, 2023;W. Ma, Chen, & Guan, 2020;Watters et al, 2021;Xin et al, 2022). Compared to IMERG, it has been well known that models have trouble simulating the precipitation realistically (D. Chen et al, 2021;Christopoulos & Schneider, 2021;Frei et al, 2003;.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The overestimation could also be related to the fact that ERA5 overestimates precipitation over high mountain ranges such as the Andes and Himalayas (Hassler & Lauer, 2021). Other studies have reported that ERA5 tends to overestimate precipitation and incorrectly identify numerous non‐precipitation events in various regions, including Austria (Sharifi et al, 2019), southern China (Gao et al, 2020), North America (Tarek et al, 2020), Iran (Yazdandoost et al, 2020), the Tibetan Plateau (Zhang et al, 2022) and the Mongolian Plateau (Xin et al, 2022). This is likely due to the limitations in the representation of cumulus parameterizations in high‐gradient mountain slopes (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Model-based meteorological products have undergone rapid development over the past few decades (Muñoz-Sabater et al, 2021). The state-of-the-art model-based dataset, ERA5-land, has been verified to have a good performance over subregions of temperate monsoon climate and temperate continental climate in China, which is the major type of the YRB (Xin et al, 2022;Xu et al, 2022). The use of ERA5-land enables a continuous and accurate representation of spatial meteorological heterogeneity, as well as the provision of additional surface indicators such as evaporation, which allows for the distributed Budyko analysis to present the runoff analysis results that are comparable to those obtained in physical models.…”
Section: Introductionmentioning
confidence: 99%